Study on Fatigue Fracture Behavior of S32750 Duplex Stainless Steel at Different Solution Temperatures - Shun Bao; Han Feng; Zhigang Song; Jianguo He; Xiaohan Wu; Yang Gu (Crystals)
This paper investigates the tensile and low-cycle fatigue characteristics of S32750 duplex stainless steel subjected to two distinct solid solution treatment temperatures. The microstructures, fracture surfaces, and slip systems of the tested steel were analyzed using optical microscopy (OM), scanning electron microscopy (SEM), and transmission electron microscopy (TEM) techniques. The findings reveal that elevating the solid solution treatment temperature from 1080 °C to 1180 °C results in an increase in the yield strength of the tested steel by approximately 36 MPa and a substantial enhancement in fatigue life by 34%. Microhardness measurements indicate that the degree of hardening in austenite post-fatigue failure significantly surpasses that of ferrite. The variation in solid solution temperature alters the ferrite and austenite content within the matrix, consequently affecting the strain distribution between the two phases. The high-temperature solid solution treatment effectively enhances the two-phase strain-bearing capacity of the tested steel. Following the 1180 °C solid solution treatment, no cloud-like dislocation patterns were observed in the ferrite; instead, they were replaced by a proliferation of thick, interwoven dislocation bundles. In contrast, the dislocations within the austenite predominantly consist of ordered planar slip and twinning. The primary contributor to the extended fatigue life is the increased number of absorbed dislocations within the ferrite grains.